Contributions to the cranial morphology of Chiromantis xerampelina Peters - Swanepoel, J. H.(Johannes Hendrik) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1964.